2020
DOI: 10.1002/essoar.10502546.2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncertainty quantification of ocean parameterizations: application to the K-Profile-Parameterization for penetrative convection

Abstract: Parameterizations of unresolved turbulent processes often compromise the fidelity of large-scale ocean models. In this work, we argue for a Bayesian approach to the refinement and evaluation of turbulence parameterizations. Using an ensemble of large eddy simulations of turbulent penetrative convection in the surface boundary layer, we demonstrate the method by estimating the uncertainty of parameters in the convective limit of the popular "K-Profile Parameterization." We uncover structural deficiencies and pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Future work could use the parameter space for comparing the behaviors of different vertical mixing schemes (KPP, TKE, GLS) and for comparing coupled and forced models. The information of the joint PDF of the three 2D projections of the 3D parameter space, given in Appendix B could also be used for choosing relevant values of forcing and preconditioning conditions (u * , B 0 , N h ) in the context of parameter tuning (Souza et al, 2020;Wagner et al, 2023). Beyond these direct applications, an interesting extension of the approach would be to evaluate the performance of the parameter space with LES data and observations.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work could use the parameter space for comparing the behaviors of different vertical mixing schemes (KPP, TKE, GLS) and for comparing coupled and forced models. The information of the joint PDF of the three 2D projections of the 3D parameter space, given in Appendix B could also be used for choosing relevant values of forcing and preconditioning conditions (u * , B 0 , N h ) in the context of parameter tuning (Souza et al, 2020;Wagner et al, 2023). Beyond these direct applications, an interesting extension of the approach would be to evaluate the performance of the parameter space with LES data and observations.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Additionally, for informative purposes, the density maps and associated joint Probability Density Functions (PDF) showing the density distribution of the values of λ s , R h , and f /N h in the three 2D projections of the 3D parameter space are given in Appendix B. This information can be useful when selecting relevant values of forcing and preconditioning conditions (u * , B 0 , N h ) in the context of parameter tuning (Souza et al, 2020;Wagner et al, 2023).…”
Section: Evaluation Of the Three-dimensional Parameter Spacementioning
confidence: 99%
“…Additionally, for informative purposes, the density maps and associated joint Probability Density Functions (PDF) showing the density distribution of the values of λ s , R h , and f /N h in the three 2D projections of the 3D parameter space are given in Appendix B. This information can be useful when selecting relevant values of forcing and preconditioning conditions (u * , B 0 , N h ) in the context of parameter tuning (Souza et al, 2020;Wagner et al, 2023).…”
Section: Evaluation Of the Three-dimensional Parameter Spacementioning
confidence: 99%
“…Kraus & Turner, 1967;Pollard et al, 1973;Price et al, 1986;Gaspar, 1988). These models have been used to derive theoretical scalings for the evolution of the MLD, such as the wind-driven deepening h ∝ u * N −1/2 t 1/2 (Pollard et al, 1973), observed empirically by Price (1979), and the free convection scal- (Turner, 1973;Van Roekel et al, 2018) measured empirically by Souza et al (2020) (h being the MLD, u * the surface friction velocity, t the time, Q the net surface heat flux and N the Brunt Väisälä frequency).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation